2017
DOI: 10.1039/c7cp04041e
|View full text |Cite
|
Sign up to set email alerts
|

Changes in dynamics of α-chymotrypsin due to covalent inhibitors investigated by elastic incoherent neutron scattering

Abstract: An essential role of enzymes is to catalyze various chemical reactions in the human body and inhibition of the enzymatic activity by small molecules is the mechanism of action of many drugs or tool compounds used to study biological processes. Here, we investigate the effect on the dynamics of the serine protease α-chymotrypsin when in complex with two different covalently bound inhibitors using elastic incoherent neutron scattering. The results show that the inhibited enzyme displays enhanced dynamics compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…This shift in the scores is visible in all PC: s but mostly in that PC2 is dominated by the cubic water phase transition at 240 K, primarily apparent in the free m AChE and m AChE-568R samples. This event is clearly associated with the Q : s around 1.59–1.81 Å –1 (demonstrated by their high loadings in Figure B) and matches with the values for ice Bragg peaks (see the Supporting Information, Table S3) and have been reported before. , To summarize the PCA for the IN6 measurements, the largest variation in the data was the temperature trend, the second largest represents the ice Bragg reflections around 1.7 Å –1 and the melting of water, and the third largest showed additional subtle difference between free and inhibited m AChE.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…This shift in the scores is visible in all PC: s but mostly in that PC2 is dominated by the cubic water phase transition at 240 K, primarily apparent in the free m AChE and m AChE-568R samples. This event is clearly associated with the Q : s around 1.59–1.81 Å –1 (demonstrated by their high loadings in Figure B) and matches with the values for ice Bragg peaks (see the Supporting Information, Table S3) and have been reported before. , To summarize the PCA for the IN6 measurements, the largest variation in the data was the temperature trend, the second largest represents the ice Bragg reflections around 1.7 Å –1 and the melting of water, and the third largest showed additional subtle difference between free and inhibited m AChE.…”
Section: Resultssupporting
confidence: 85%
“…Huperzine A has been shown to not affect or possibly increase , the dynamics of human AChE ( h AChE), whereas the covalent inhibitor soman decreased its dynamics . The same ligand-dependent trend has been observed for other protein–inhibitor complexes using nuclear magnetic resonance (NMR) or neutron scattering, where complex formation led to increased or decreased dynamics. , …”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Andersson et al . (2017) investigated the effect of two different inhibitors, namely TPCK and chymostatin, on the dynamics of the serine protease α -chymotrypsin. From the analysis of the EINS signal, the authors concluded that the inhibited enzymes underwent a dynamical transition at lower temperatures and in a more cooperative way leading to bigger amplitudes of motions at higher temperatures (up to 310 K).…”
Section: Resultsmentioning
confidence: 99%
“…From the analysis of the EINS signal, the authors concluded that the inhibited enzymes underwent a dynamical transition at lower temperatures and in a more cooperative way leading to bigger amplitudes of motions at higher temperatures (up to 310 K). Andersson and collaborators deduced that the inhibitor either directly allows for larger amplitudes of the enzyme motions, or influences the water network around the enzymes in a way that permits more degrees of motional freedom leading to a lowering of the potential energy barrier seen by the enzyme atoms (Andersson et al ., 2017).…”
Section: Resultsmentioning
confidence: 99%